2001
DOI: 10.1590/s0066-782x2001000700006
|View full text |Cite
|
Sign up to set email alerts
|

Chagas' heart disease: evolutive evaluation of electrocardiographic and echocardiographic parameters in patients with the indeterminate form

Abstract: Objective -To identify and associate potential electrocardiographic and echocardiographic changes in pa-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
1
23

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 20 publications
6
50
1
23
Order By: Relevance
“…Although, statistical significance was obtained for seropositive subjects with ECG alterations, definitive conduction defect associated with positive serology was present only in 16% of them. Similar low percentage was also reported in a recently published paper studying Brazilian chronic infected subjects, those who developed conduction defects like RBBB, LBBB, atriventricular blockage, or all of them (Ianni et al 2001). In general, the indeterminate form of Chagas disease recognized in our population is similar to those reported in South America.…”
Section: Discussionsupporting
confidence: 91%
“…Although, statistical significance was obtained for seropositive subjects with ECG alterations, definitive conduction defect associated with positive serology was present only in 16% of them. Similar low percentage was also reported in a recently published paper studying Brazilian chronic infected subjects, those who developed conduction defects like RBBB, LBBB, atriventricular blockage, or all of them (Ianni et al 2001). In general, the indeterminate form of Chagas disease recognized in our population is similar to those reported in South America.…”
Section: Discussionsupporting
confidence: 91%
“…Figure 1 shows the locations of the various field areas that have been or are being studied. There is a great variation of morbidity from one area to other [89][90][91] . From 1999 onwards, we started to classify the areas into two categories: A) areas of high morbidity; and B) areas of low morbidity 92 .…”
Section: Morbidity Differences In Chagas Disease According To Geograpmentioning
confidence: 99%
“…Even though some abnormalities may appear in the ECG and in the echocardiogram. The indeterminate form of Chagas disease clearly represents a benign condition with a long-term prognosis 90 .…”
Section: Areas Of Low Morbiditymentioning
confidence: 99%
“…Up to 60% of infected patients have no evidence suggesting cardiovascular or gastrointestinal involvement. These individuals are thought to have what is known as the indeterminate form of the disease (1). Previous longitudinal studies of such patients have revealed percentages www.bjournal.com.br of electrocardiographic changes ranging from 23 to 38% during long-term follow-up (2,3).…”
mentioning
confidence: 99%